Analysis of Epistemological Barriers in Students' Problem-Solving of Basic Algebra in Junior High School through the Didactical Design Research (DDR) Approach - Khafid Putranto; Markus Palobo; Kamariah Kamariah (Riemann: Research of Mathematics and Mathematics Education, 2025)
Algebra is a fundamental topic in junior secondary mathematics, yet many students experience difficulties, particularly in solving algebra word problems. This study aims to analyze the epistemological obstacles encountered by eighth-grade students in solving basic algebra word problems using the Didactical Design Research (DDR) framework. A descriptive qualitative approach was employed with two eighth-grade students of SMP Muhammadiyah Merauke representing high and low cognitive ability levels. Data were collected through a written algebra word problem based on Polya’s problem-solving stages and face-to-face recorded interviews. The findings indicate that students experience epistemological obstacles in interpreting problem contexts, understanding variables as general quantities, and reflecting on the correctness of algebraic models. These obstacles occur in both high- and low-ability students, suggesting that procedural skills are not always supported by meaningful conceptual understanding.